The Dynamics of Timor-Leste's Foreign Aid Dependence and its Implications : JEL Classification: F35, O11, O19, O20, P45 - Evan Ilham Pasha; Muhammad Riza Hanafi (Journal La Bisecoman, 2026)
In this paper, the dependency theory approach has been used to analyze how East Timor has been economically dependent on world powers after its independence in the year 2002 through the aid. Although East Timor has had its fair share of oil deposits, it is plagued with major challenges in terms of damaged infrastructure as a result of the long conflict forcing the country to be under foreign aid. This study will be looking at the effects of the aid provided by the United Nations, the World Bank, and donor countries in terms of creating institutional dependency by the imposition of preconditions that usually serve the advantage of the aid givers. Moreover, change in dependency of the traditional actors towards China through the Belt and Road Initiative program as also a part of this research with consequences to the geopolitical and economic policy of East Timor. As revealed in the conclusion of the current paper, East Timor remains entangled in an exploitative global economic system as a peripheral state, just as it has been the case since its inception and as it was the case with the unbalanced power relations in the international system.